Studies on local isolates of neisseria gonorrhoeae:role in different clinical populations antimicrobial profile and mechanisms of resistance - De Jongh, Mari (University of Limpopo (Medunsa Campus), 2010)
Studies were performed on local isolates of Neisseria gonorrhoeae to assess their aetiological role in different clinical populations, to determine the evolution of antimicrobial resistance and characterisation of quinolone resistance. In the study performed on women presenting for termination of pregnancy (TOP) the prevalence of common sexually transmitted pathogens (Neisseria gonorrhoeae, Chlamydia trachomatis and Trichomonas vaginalis) was much higher than reported from other studies in TOP populations. The commonest organism isolated was C. trachomatis. There were no significant differences in infection rates in women with or without signs and symptoms of vaginal discharge. Therefore all women presenting for TOP need to be screened and treated for sexually transmitted pathogens. In the study to determine the co-infection rates in men presenting with urethritis (discharge and/or burning on micturition (BOM)), the overall infection rate was 65% with co-infections (more than one pathogen detected) in 8%. N. gonorrhoeae was found in 45%, C. trachomatis in 15% and T. vaginalis in 6% of the men. T. vaginalis was found in higher percentages in men with BOM only, in the absence of visible discharge. There may be a need to add an anti-trichomonicidal agent in men presenting with BOM only. When comparing sexual partners and the pathogens isolated, significantly fewer pathogens were detected in males that had their wives as sole contact when comparing them to men who had sex with casual contacts, reflecting high sexual risk behaviour. M DE JONGH Page xi PhD Med Microbiology N. gonorrhoeae isolates were obtained from men presenting to a general practitioner in Pretoria with urethral discharge. The antimicrobial susceptibility profile was determined to currently used, previously used and potential antimicrobial agents by the disk diffusion, Etest and agar dilution methods. High-level ciprofloxacin resistance emerged in the Pretoria region at 7%. No isolate showed a MIC value of intermediate resistance, suggesting importation of resistant strains, rather than a step-wise incremental increase. Penicillin-resistant gonococcal isolates are entrenched in the community; overall there was 32% resistance (MIC≥2μg/mℓ), with 16% due to penicillinase-producing (PPNG) isolates. Tetracycline-resistant isolates has increased dramatically at 54% and with 36% showing high-level (plasmid-mediated) resistance. All isolates remained susceptible to ceftriaxone, cefoxitin and cefpodoxime. Local gonococcal isolates were sequenced using Neisseria gonorrhoeae Multi-Antigen Sequence Typing (NG-MAST). In this study a total of 18 isolates resolved into 13 different sequence types (STs). A cluster of four isolates of known sequence type, ST217, was found. Two other known sequence types (ST189 & ST523) have previously been seen in Durban. The ten quinolone-resistant isolates resolved into six STs, five of which were new STs and one cluster of four isolates of a known sequence type. This demonstrates the heterogeneity of ciprofloxacin-resistant strains suggesting introduction of strains from multiple sources rather than clonal spread of a single strain.
Thesis (PhD Med.(Microbiology))--University of Limpopo, 2010.
Keywords: Neisseria gonorrhoeae; Antimicrobial